Societal satisfaction and acceptance in light of modern planning trends Between man (collective consciousness) and place (material content) Towards preliminary planning guides - صيداوي, رانيا (Latakia University Journal -Engineering Sciences Series, 2023)
The forms of urban planning have multiplied and the ideas that paved the way for the modernity of its multiple vectors in a future vision towards achieving cities that enjoy vitality and increase the viability of its users steadily increase through the application of those ideas based on a societal vision reinforced by data of frequent change at the level of place (material content) and human (consciousness). collective) in light of the interactive exchange between them and the resulting measurable positive or negative effects and within a general framework that guarantees social satisfaction and acceptance in those communities and bestows on them a spectrum of future visions that are more appropriate and compatible with their residents. The research comes within the framework of trying to find preliminary planning directives to measure the amount of community satisfaction and acceptance of this planning reality in residential areas and ways or directives to enhance it, thus forming a first brick in the path of ensuring positive interaction between the community environment with its collective awareness and its physical planning content, while leaving the field open for the possibility of evaluation and improvement towards achieving A more stable urban community environment in the face of continuous changes.